Hydroxysafflor Yellow A Ameliorates Myocardial Ischemia/Reperfusion Injury by Suppressing Calcium Overload and Apoptosis. (21st May 2021) - Ye, Jingxue; Wang, Ruiying; Wang, Min; Fu, Jianhua; Zhang, Qiong; Sun, Guibo; Sun, Xiaobo
Abstract : Myocardial ischemia/reperfusion injury (MI/RI) is an urgent problem with a great impact on health globally. However, its pathological mechanisms have not been fully elucidated. Hydroxysafflor yellow A (HSYA) has a protective effect against MI/RI. This study is aimed at further clarifying the relationship between HSYA cardioprotection and calcium overload as well as the underlying mechanisms. We verified the protective effect of HSYA on neonatal rat primary cardiomyocytes (NPCMs) and human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) from hypoxia-reoxygenation (HR) injury. To explore the cardioprotective mechanism of HSYA, we employed calcium fluorescence, TUNEL assay, JC-1 staining, and western blotting. Finally, cardio-ECR and patch-clamp experiments were used to explain the regulation of L-type calcium channels (LTCC) in cardioprotection mediated by HSYA. The results showed that HSYA reduced the levels of myocardial enzymes and protected NPCMs from HR injury. HSYA also restored the contractile function of hiPSC-CMs and field potential signal abnormalities caused by HR and exerted a protective effect on cardiac function. Further, we demonstrated that HSYA protects cardiomyocytes from HR injury by decreasing mitochondrial membrane potential and inhibiting apoptosis and calcium overload. Patch-clamp results revealed that MI/RI caused a sharp increase in calcium currents, which was inhibited by pretreatment with HSYA. Furthermore, we found that HSYA restored contraction amplitude, beat rate, and field potential duration of hiPSC-CMs, which were disrupted by the LTCC agonist Bay-K8644. Patch-clamp experiments also showed that HSYA inhibits Bay-K8644-induced calcium current, with an effect similar to that of the LTCC inhibitor nisoldipine. Therefore, our data suggest that HSYA targets LTCC to inhibit calcium overload and apoptosis of cardiomyocytes, thereby exerting a cardioprotective effect and reducing MI/RI injury.